The Tumor Microenvironment of DLBCL in the Computational Era - Opinto, Giuseppina; Vegliante, Maria Carmela; Negri, Antonio; Skrypets, Tetiana; Loseto, Giacomo; Pileri, Stefano Aldo; Guarini, Attilio; Ciavarella, Sabino (Frontiers in Oncology, 2020)
Among classical exemplifications of tumor microenvironment (TME) in lymphoma pathogenesis, the “effacement model” resembled by diffuse large B cell lymphoma (DLBCL) implies strong cell autonomous survival and paucity of non-malignant elements. Nonetheless, the magnitude of TME exploration is increasing as novel technologies allow the high-resolution discrimination of cellular and extra-cellular determinants at the functional, more than morphological, level. Results from genomic-scale studies and recent clinical trials revitalized the interest in this field, prompting the use of new tools to dissect DLBCL composition and reveal novel prognostic association. Here we revisited major controversies related to TME in DLBCL, focusing on the use of bioinformatics to mine transcriptomic data and provide new insights to be translated into the clinical setting.